A baroque library: the bibliographic collection of the Marquises of Beniel in 1710 - García Cuadrado, Amparo (Historia y Memoria de la Educación, 2017)
This article deals with the study of a noble’s library, through the inventory carried out upon the death of the Italian aristocrat Eleonora Gonzaga in 1710. An analysis of the titles, compiled by the notary, shows the baroque character of the collection, a small library which represents the reading tastes of the Marquises of Beniel. This library, shared by the couple, within a very specific domestic space, wasnot simply a property of its owners, but was read by them, as is demonstrated by a second inventory drawn up in 1727. The abundance of historical texts, complemented by tomes on political-moral didacticism and, to a lesser extent, religious books, comprise a bibliographic collection that seems to have been rare among the moderate-level Murcian nobility. Such reading trends may be indicative of the intellectual, moral, and political interests that would have governed the vital trajectory of its owners in the public and private domain. The books printed in Italian also bring us closer to the personality of the aristocrat whose mother tongue would remain linked to her daily devotions. The ordinary appearance of most of the copies may be indicative of the utilitarian nature of the collection in the formation and leisure of the aristocrat and her family; these were books that served for religious practice, poetic delight and the historical, moral and political formation of the reader.